Metabolic derangements and its association with the level of physical activity in obese and overweight children aged 8-14 years at Teaching Hospital, Jaffna - Thavaranjiny, S.; Umasankar, N.; Sathiadas, M.G. (The Jaffna Medical Association, 2023)
Childhood obesity is a rapidly growing nutritional disorder in children. Metabolic derangements are a common problem encountered in these children. Research has shown the relationship between dietary intake and metabolic derangement. We undertook this study to see the relationship between metabolic derangements and the level of physical activity. We aimed to assess the relationship of metabolic derangements and the level of physical activity among obese and overweight children. A hospital-based descriptive cross-sectional study was done in outpatient Paediatric clinics at the Teaching Hospital Jaffna. Children aged 8- 14 years with BMI above + 1SD were included in this study. The pattern of physical activity was assessed using a Physical Activity Questionnaire-S. Anthropometric measurements were taken using standard procedures and details of the laboratory investigations were obtained from the clinic record done within the immediate past six months. A total of 280 children were included. Nearly two-thirds of children were obese 63.9% (n-178), and 8.6% (n-24) and 2.9% (n-8) of children have impaired glucose and DM respectively; 23.2% (n-64) of the children had equal or more than 90th centile diastolic blood pressure, and 35% (n-98) had equal or more than 90th centile systolic blood pressure and waist circumference. Insufficient physical activity was seen in 44.3% (n-124) and 13.2% (n- 37) of these children had metabolic syndrome.
Keywords: Overweight; Obese; Children; Metabolic derangement; Activity level